Tweeting from the Town Square: Measuring Geographic Local Networks - Yardi, Sarita; boyd, danah (International Conference on Weblogs and Social Media, 2010)
This paper examines tweets about two geographically local events—a shooting and a building collapse—that took place in Wichita, Kansas and Atlanta, Georgia, respectively. Most Internet research has focused on examining ways the Internet can connect people across long distances, yet there are benefits to being connected to others who are nearby. People in close geographic proximity can provide real-time information and eyewitness updates for one another about events of local interest. We first show a relationship between structural properties in the Twitter network and geographic properties in the physical world. We then describe the role of mainstream news in disseminating local information. Last, we present a poll of 164 users’ information seeking practices. We conclude with practical and theoretical implications for sharing information in local communities.